Central nervous system involvement at first relapse in patients with acute promyelocytic leukemia treated with all-trans retinoic acid and anthracycline monochemotherapy without intrathecal prophylaxis - Pau Montesinos; Joaquín Díaz-Mediavilla; Guillermo Debén; Virginia Prates; Mar Tormo; Vicente Rubio; Inmaculada Pérez; Isolda Fernández; Maricruz Viguria; Chelo Rayón; José González; Javier de la Serna; et al. (Haematologica, 2009)
Background The prevalence of and risk factors for central nervous system recurrence in patients with acute promyelocytic leukemia are not well established and remain a controversial matter.Design and Methods Between 1996 and 2005, 739 patients with newly diagnosed acute promyelocytic leukemia enrolled in two consecutive trials (PETHEMA LPA96 and LPA99) received induction therapy with all-trans retinoic acid and idarubicin. Consolidation therapy comprised three courses of anthracycline monochemotherapy (LPA96), with all-trans retinoic acid and reinforced doses of idarubicin in patients with an intermediate or high risk of relapse (LPA99). Central nervous system prophylaxis was not given.Results Central nervous system relapse was documented in 11 patients. The 5-year cumulative incidence of central nervous system relapse was 1.7% (LPA96 3.2% and LPA99 1.2%; p=0.09). The cumulative incidence was 0%, 0.8%, and 5.5% in low-, intermediate-, and high-risk patients, respectively. Relapse risk score (p=0.0001) and the occurrence of central nervous system hemorrhage during induction (5-year cumulative incidence 18.7%, p=0.006) were independent risk factors for central nervous system relapse.Conclusions This study shows a low incidence of central nervous system relapse in patients with acute promyelocytic leukemia following therapy with all-trans retinoic acid and anthracycline without specific central nervous system prophylaxis. Central nervous system relapse was significantly associated with high white blood cell counts and prior central nervous system hemorrhage, which emerged as independent prognostic factors.